Do Epidural Catheter Size and Flow Rate Affect Bolus Injection Pressure in Different Programmed Intermittent Epidural Bolus Regimens? An In Vitro Study. (December 2019) - Krawczyk, Paweł; Piwowar, Piotr; Sałapa, Kinga; Lonc, Tomasz; Andres, Janusz
Abstract : BACKGROUND: The optimal programmed intermittent epidural bolus regimen for labor analgesia remains unknown. Some studies indicate that better drug spread in the epidural space results from greater injection pressure; however, there is a lack of data regarding the maximum pressure generated by epidural bolus injection using different catheters and flow rates. METHODS: We evaluated the flow and pressure characteristics of 11 commonly used epidural catheters combined with 3 different infusion pumps that deliver epidural infusions according to the programmed intermittent epidural bolus regimen. Pressure changes were measured over time at flow rates of 100, 250, and 400 mL·hour −1 and with a bolus volume of 10 mL. To account for repeated measures, linear mixed models were used. Features were selected with a backward stepwise procedure continued until only statistically significant variables were left in the model. RESULTS: We performed 660 measurements. The mean maximal pressure generated during bolus injection ranged from 86 to 863 mm Hg for different flow rates and catheter designs. The interaction between flow rate and catheter gauge resulted in 1.31, 1.65, and 2.00 mm Hg of pressure increase for 18G, 19G, and 20G catheters, respectively, per 1 mL·hour −1 of increased flow rate ( P < .001). Analyses including wire-reinforced catheters revealed a 1.16, 1.76, and 2.36 mm Hg pressure increase for 18G, 19G, and 20G catheters, respectively, per 1 mL·hour −1 of increased flow rate ( P < .001). In some cases, it triggered the occlusion pump alarm. CONCLUSIONS: Significant differences were observed in the in vitro maximum pressure value among the various catheter and flow rate combinations with a higher pressure value for wire-reinforced catheters used in the study. The optimal flow rate and epidural catheter combination may allow for delivery of the bolus with high flow rate without triggering the occlusion alarm.